2019
DOI: 10.1088/1755-1315/388/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive phytochemical compound of (Cyperus iria L.) By using gas chromatography –mass spectrometry

Abstract: Fifty three phytochemical compound in the methanolic extract were identified of Cyperus iria L. The identification is based on the molecular weight, peak area, MS Fragmentation and, retention time,.GC-MS analysis of Cyperus iria L. found the presence of the compounds : (2S,3S)-2,3-Dihydroxy-2-isopropylbutyric acid [(5R,6S)-6-hydroxy-1-azabicyclo[3.3.0]oct-3-en-4-yl]methyl : 1,2,4-Benzenetriol : 4-Mercaptophenol : 2-Pyrazoline,5-ethyl-1,4-dimethyl : 5-Hydroxymethylfurfural : 2-pyrazoline,5-ethyl-1,4-dimethyl : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Among the compounds 9‐octadecenoic acid methyl ester, (E)‐ exhibits the highest score (−0.401 kcal/mol) against urate oxidase receptor and 9‐hexadecenoic acid methyl ester, (Z)‐ found to have highest docking score (−1.449 kcal/mol) against glutathione reductase receptor. Earlier researcher showed that 9‐octadecenoic acid methyl ester and 9‐hexadecenoic acid methyl ester have antioxidant activity (Shaheed et al., 2019). It has been proven that the negative and low value of the free energy of binding demonstrates a strong favorable bond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the compounds 9‐octadecenoic acid methyl ester, (E)‐ exhibits the highest score (−0.401 kcal/mol) against urate oxidase receptor and 9‐hexadecenoic acid methyl ester, (Z)‐ found to have highest docking score (−1.449 kcal/mol) against glutathione reductase receptor. Earlier researcher showed that 9‐octadecenoic acid methyl ester and 9‐hexadecenoic acid methyl ester have antioxidant activity (Shaheed et al., 2019). It has been proven that the negative and low value of the free energy of binding demonstrates a strong favorable bond.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier researcher showed that 9-octadecenoic acid methyl ester and 9-hexadecenoic acid methyl ester have antioxidant activity (Shaheed et al, 2019). It has been proven that the negative and low value of the free energy of binding demonstrates a strong favorable bond.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the bioactive compounds exhibited, cholest-4-en-6on-3-ol has the highest 63.7% retention time (24.58 min) and has anti-obesity activity (Shaheed et al, 2019). At the same time, another compound, Lupeol, was observed during prolonged retention (35.9 min), and the maximum area percentage was 7.36% (Figure 2).…”
Section: Gc-ms Analysis Of Root Methanolic Extractmentioning
confidence: 97%
“…The compounds like cholestan-3-one-4,4dimethyl-(5α); 9-octadecenoic acid(Z)-phenyl methyl ester; (9Z)-octadec-9-enoic acid (Oleic acid); androst1-en-3one,4,4-dimethyl-(5α) identified to possess anti-cancer, antiinflammatory, antioxidant, antiulcer genic, antipyretic activities in various plant extracts of medicinally important plants (Safwat et al, 2018;Shelke & Bhot, 2019;Yamuna et al, 2017;Yue et al, 2020). Cholest-4-en-6-on-3-ol and Lupeol are the two identified compounds with highest percent of compounds among all the compounds in root methanolic extracts of M. calabura and reported to possess anticancer, antioxidant, anti-prostate, anti-inflammatory activities in different plant extracts of medicinal plants (Geetha & Varalakshmi, 2001;Shahaby et al, 2019;Shaheed et al, 2019;Yang et al, 2020). There are a few identified compounds, 1,12-Dibromododecane; 5-(2-bromopropan-2-yl)-2-methylcyclohexan-1-ol;…”
Section: Gc-ms Analysis Of Root Methanolic Extractmentioning
confidence: 99%
“…Berfungsi sebagai agen antiperadangan, antikanker, bahan industri barang pecah belah [28,29] N-methyl-1adamantaneacetamide Antioksidan, antimikroba, antikanker, antiinflamasi, antihelmintik (anti parasit yang disebabkan oleh cacing) dan antiinflamasi [41] Silicone grease, Silikonfett…”
Section: -Ethylacridineunclassified